GENETIC VARIABILITY AND DROUGHT PARAMETERS AMONG SOME GRAIN SORGHUM GENOTYPES USING QUANTITATIVE TRAITS AND RAPD MARKERS - Bahaa A. Zarea; M.E.M. El-Sagheer; H.M. Hafez; A.Y.M. Ahmed (Big Data in Agriculture)
Genetic diversity is one of the main elements in the enhancement of many crop plants, including sorghum,. For that twenty grain sorghum genotypes were evaluated at Shandaweel Agricultural Research Station, Sohag governorate, Egypt, during the summer season of 2022 in two experiments (normal irrigation 100% and severe water stress 40% of the optimum) for assessment of the variability among these genotypes, RAPD molecular markers and drawing the phylogenetic tree using cluster analysis. The results indicated highly significant differences among the genotypes, irrigation treatments and their interaction for all traits, suggesting that these genotypes were highly variable, therefore, would respond to selection. , the genotypes G3, G7, G8, G13 and G16 gave the best performance for grain yield/plant under both environments and their combined data. These genotypes will be testing in a large scale. High genetic advance as a percentage of mean (Δg%) was obtained for plant height and 1000 grain weight and moderate for 50% flowering and grain yield/plant. High GCV% and PCV% revealed for plant height, moderate for 1000-grain weight, and low for 50% flowering and grain yield/plant., this demonstrates that the genotypes have a diverse genetic background as well as the capacity to respond favorably to selection. The Results of RAPD molecular markers showed that the percent of polymorphism (%P) were between 44.44 to 77.78 with an average of 59.78%. The number of polymorphic bands ranged from 4 to 12 with an average of 6.38 bands per primer. The bands size was from 259 bp to 2318 bp, generated by OPA-18 and OPH-01 primers, respectively. The Polymorphism information content (PIC) values varied from 0.10 to 0.28 with an average of 0.20. While marker index (MI) varied from 0.40 to 2.76 with an average of 1.31. In this trend the results revealed that the resolving power (Rp) varied from 1.10 (OPA-18 & OPAV-13) to 5.20 (OPG-09) with an average of 2.90. Single-marker analysis (SMA) indicated that three of the RAPD markers identified in this study showed significant association with the two traits viz., plant height and 1000-grain weight under normal and drought environments conditions. The cluster analysis based on RAPD and means of morphological data showed similarity coefficient values ranged from 0.64 to 0.92 with an average similarity index of 0.78. The Mantel test revealed, there was positive and non-significant correlation between the genetic distances based on phenotypic data and the similarity data based on RAPD markers, (r= 0.07, P< 0.05) and (r= 0.03, P< 0.05) under normal and drought conditions, respectively.